Experimental Determination of Temperature During Rotary Friction Welding of AA1050 Aluminum with AISI 304 Stainless Steel - Eder Paduan Alves; Francisco Piorino Neto; Chen Ying An; Euclides Castorino da Silva (Journal of Aerospace Technology and Management, 2012)
The purpose of this study was the temperature monitoring at bonding interface during the rotary friction welding process of dissimilar materials: AA1050 aluminum with AISI 304 stainless steel. As it is directly related to the mechanical strenght of the junction, its experimental determination in real time is of fundamental importance for understanding and characterizing the main process steps, and the definition and optimization of parameters. The temperature gradients were obtained using a system called Thermocouple Data-Logger, which allowed monitoring and recording data in real-time operation. In the graph temperature versus time obtained, the heating rates, cooling were analyzed, and the maximum temperature was determined that occurred during welding, and characterized every phases of the process. The efficiency of this system demonstrated by experimental tests and the knowledge of the temperature at the bonding interface open new lines of research to understand the process of friction welding.